2023
DOI: 10.1039/d2nh00565d
|View full text |Cite
|
Sign up to set email alerts
|

A light-operated integrated DNA walker–origami system beyond bridge burning

Abstract: Integrating rationally designed DNA molecular walkers and DNA origami platforms is a promising route towards advanced nano-robotics of diverse functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The field of rationally designed DNA molecular motors has advanced from early simplistic burning-bridge DNA molecular walkers to sophisticated DNA molecular motors capable of sustainable, scalable, and directional action under light irradiations or with supply of chemical fuels. These advanced DNA molecular motors produce nontrivial force (a few piconewtons per motor from a recent single-molecule study) and were recently integrated , with DNA origami successfully. In the long run, the marriage between the force-capable DNA molecular motors and the DNA nanotechnology of rich designability and versatile integrability with other materials (peptides, synthetic polymers, etc.)…”
Section: Research Focus 3: Bioinspired Hierarchical Materials/devicesmentioning
confidence: 99%
“…The field of rationally designed DNA molecular motors has advanced from early simplistic burning-bridge DNA molecular walkers to sophisticated DNA molecular motors capable of sustainable, scalable, and directional action under light irradiations or with supply of chemical fuels. These advanced DNA molecular motors produce nontrivial force (a few piconewtons per motor from a recent single-molecule study) and were recently integrated , with DNA origami successfully. In the long run, the marriage between the force-capable DNA molecular motors and the DNA nanotechnology of rich designability and versatile integrability with other materials (peptides, synthetic polymers, etc.)…”
Section: Research Focus 3: Bioinspired Hierarchical Materials/devicesmentioning
confidence: 99%
“…DNA origami technology also provides a sub-microscale platform to guide their locomotion. Wang and co-workers have demonstrated that by driving an advanced light-powered DNA bipedal walker on a rod-shaped DNA origami platform approximately 170 nm in length [325]. Clever use of the fluorescent method allowed the researchers to analyze the self-directed, processual motion of the DNA molecular walker, which, although somewhat more complex on the surface of the DNA oligomers, essentially exhibits the motion of a translational molecular motor.…”
Section: Molecular Machine In Surface Spacementioning
confidence: 99%